Geospatial information systems for Karst: Morpho-Geological Study in Kinta Valley, Perak, Malaysia - Muhammad, Ros Fatihah; Alkouri, Omar (Malaysian Journal of Science, 2009)
The Kinta Valley karst has gone thourgh process of natura; and human-iduced degradation. The topography and lithology in this area has made it possible for accelerated limestone dissolution and the marble has been quarried for many years. The geospatial study to observe the changes in the jarst for over 23 years has been carried out. A databased of sinkhole distribution was created and the changes of limestone topography were analyzed as well as teh other relatively important features. The intersification of natural denudation rate and human activities has given huge impact on the kars. it can be observed byt spatial temporal data model that also has facilitated the delineation of the changes in the topography.